Editorial: thiopurines in the multidrug era—time to rescue our memories over half a century of experience. Authors' reply. Issue 6 (22nd August 2022) - Rezazadeh Ardabili, Ashkan; Jeuring, Steven; Mujagic, Zlatan; Oostenbrug, Liekele; Romberg‐Camps, Mariëlle; Jonkers, Daisy; Van Bodegraven, Adriaan; Pierik, Marieke
Abstract : LINKED CONTENT This article is linked to Rezazadeh Ardabili et al papers. To view these articles, visit https://doi.org/10.1111/apt.17128 and https://doi.org/10.1111/apt.17164